Variations in Size of Sugarcane Bagasse Fiber as Raw Material for Making Environmentally Friendly Plates - Rusdianto, Andrew Setiawan; Lindriati, Triana; Oscalani, Queny (International Journal on Food, Agriculture and Natural Resources, 2024)
Plastic is a material that is often used as a storage medium, equipment and also furniture to support human activities, but plastic is not easily broken down by the environment. Bioplastic technology is one of the efforts made to address the problem of plastic packaging which can pollute the environment. Environmentally friendly plates, bioplastic products made from tapioca, glycerol and sugar cane bagasse. This research aims to determine the effect of variations in the size of bagasse on tensile strength, elongation at break, water resistance and biodegradability of environmentally friendly plates and to obtain the best formulation of varying sizes of bagasse as raw material for making environmentally friendly plates. This research used a Completely Randomized Design (CRD) with one factor, namely variation in the size of the bagasse. The results of this research show that there is a real influence between tensile strength, water resistance and biodegradability, however, in the elongation test, variations in bagasse did not have a significant effect. Tensile strength values range from 20.00 N/mm2 to 47.72 N/mm2. The largest elongation value is 4.08%. The highest water resistance is at room temperature, namely 88.86% with a degree of curvature of 16⁰ and in water with a temperature of 60⁰C, namely 85.02% with a degree of curvature of 18.75⁰. Variations in the size of bagasse also affect the biodegradability of environmentally friendly plates which ranges from 11.77% to 14.65%. The best treatment is a sample with a variety of bagasse sizes of 60 mesh, because it has high strength compared to other samples.